2017
DOI: 10.1016/j.eurpsy.2017.01.1828
|View full text |Cite
|
Sign up to set email alerts
|

Surviving psychiatry on-calls

Abstract: IntroductionOut of hours, there is only one on-site junior doctor. First year psychiatry trainees (CT1s) and GP trainees may have no prior experience in psychiatry. On-call shifts are therefore potentially daunting for new trainees.ObjectivesExpand the resources available for trainees when on-call.MethodsWe issued questionnaires to CT1s asking if they would have appreciated more information about on-call scenarios and in what format.Based on the questionnaire results we implemented some changes. These were:– a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…7 Prior research has demonstrated that many junior doctors perceive themselves to lack knowledge, skills and confidence for assessing mental health patients. 8, 9 Holt et al found that 63% of first-year core psychiatry trainees were 'neutral' or 'disagreed' that they felt prepared for on-call shifts in the specialty. 9 This may be partly because of the wide variation in coverage of psychiatry at UK medical schools and/or a lack of recent exposure to the specialty.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…7 Prior research has demonstrated that many junior doctors perceive themselves to lack knowledge, skills and confidence for assessing mental health patients. 8, 9 Holt et al found that 63% of first-year core psychiatry trainees were 'neutral' or 'disagreed' that they felt prepared for on-call shifts in the specialty. 9 This may be partly because of the wide variation in coverage of psychiatry at UK medical schools and/or a lack of recent exposure to the specialty.…”
Section: Introductionmentioning
confidence: 99%
“… 8 , 9 Holt et al found that 63% of first-year core psychiatry trainees were ‘neutral’ or ‘disagreed’ that they felt prepared for on-call shifts in the specialty. 9 This may be partly because of the wide variation in coverage of psychiatry at UK medical schools and/or a lack of recent exposure to the specialty. 10 For foundation trainees, the transition from student to doctor can also present additional challenges and represent a time of stress and low confidence, emphasising their need for support, training and effective placement induction.…”
Section: Introductionmentioning
confidence: 99%